ANALISIS YURIDIS KEWENANGAN MAJELIS ULAMA INDONESIA DALAM PENYELENGGARAAN JAMINAN PRODUK HALAL - amri, syaiful; Jamil, M.; ., Ardiansyah (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2017)
Halal’s product become an interesting issue. Especially talking about MUI’s Authority in the implementation of Halal Products Guarantee, it’s the main conversation in several media to. Three of main focus in this study are: 1) The legal basis of MUI in the implementation of Halal Product Guarantee, 2) MUI’s Authority under applicable law, and 3) Implementation of regulations concerning the implementation of Halal Product Guarantee. The government always publishing new Law that be set for the interests of the mass interest, but sometimes it becomes disaster for several parties. Juridically, this paper will explores the legal position of MUI about its authority in the implementation of Halal Product Guarantee in Indonesia. Kata Kunci: Kewenangan, Implementasi, Majelis Ulama Indonesia, Jaminan Produk Halal